2009
DOI: 10.1051/0004-6361/200913605
|View full text |Cite
|
Sign up to set email alerts
|

Probing the evolution of molecular cloud structure

Abstract: Context. Probability distribution of densities is a fundamental measure of molecular cloud structure, containing information on how the material arranges itself in molecular clouds. Aims. We derive the probability density functions (PDFs) of column density for a complete sample of prominent molecular cloud complexes closer than d < ∼ 200 pc. For comparison, additional complexes at d ≈ 250−700 pc are included in the study. Methods. We derive near-infrared dust extinction maps for 23 molecular cloud complexes, u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

91
601
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 431 publications
(693 citation statements)
references
References 34 publications
(35 reference statements)
91
601
1
Order By: Relevance
“…We do not have direct access to the 3D (volume) density from observations-only to the 2D (column) density distribution (Berkhuijsen & Fletcher 2008;Kainulainen et al 2009;Lombardi et al 2011;Schneider et al 2012Schneider et al , 2013Hughes et al 2013;Kainulainen & Tan 2013;Berkhuijsen & Fletcher 2015;Schneider et al 2015). However, one can estimate the 3D density dispersion and the 3D density PDF by extrapolating the 2D density information given in the plane of the sky to the third dimension (along the line of sight), assuming isotropy of the clouds (Brunt et al 2010a(Brunt et al , 2010bKainulainen et al 2014).…”
Section: Density Pdf and Conversion From Twomentioning
confidence: 99%
“…We do not have direct access to the 3D (volume) density from observations-only to the 2D (column) density distribution (Berkhuijsen & Fletcher 2008;Kainulainen et al 2009;Lombardi et al 2011;Schneider et al 2012Schneider et al , 2013Hughes et al 2013;Kainulainen & Tan 2013;Berkhuijsen & Fletcher 2015;Schneider et al 2015). However, one can estimate the 3D density dispersion and the 3D density PDF by extrapolating the 2D density information given in the plane of the sky to the third dimension (along the line of sight), assuming isotropy of the clouds (Brunt et al 2010a(Brunt et al , 2010bKainulainen et al 2014).…”
Section: Density Pdf and Conversion From Twomentioning
confidence: 99%
“…PDFs of mass surface density (or N H or A V ) have been used as tools to study the physical characteristics of observed molecular clouds and IRDCs (e.g., Kainulainen et al 2009;Kainulainen & Tan 2013;Butler et al 2014). Mechanisms such as turbulence, self-gravity, shocks, and magnetic fields all contribute to the resulting distribution of Σ.…”
Section: Mass Surface Density Pdfsmentioning
confidence: 99%
“…Those PDFs have been characterised by a lognormal at low column densities which becomes dominated by a power law tail at the high end (Kainulainen et al 2009;Schneider et al 2013Schneider et al , 2015Benedettini et al 2015). The presence of the lognormal component has, however, been questioned by Lombardi et al (2015) who argue that column density PDFs of molecular clouds can be accounted for entirely by truncated power laws.…”
Section: Relationship To Unbound Starless Coresmentioning
confidence: 99%